Lantaldea - _____, _____ (Osagaiz: osasun-zientzien aldizkaria, 2018)
Zuzendaria Jose Ramon Furundarena Erredakzio Batzordea Karlos Ibarguren Eukene Ansuategi Izaskun Elezgarai Angel Bidaurrazaga Marimar Ubeda Miren Altuna Batzorde Zientifikoa Iker Badiola Gaizka Bilbao Rafael Aldabe Juanjo Aurrekoetxea Garazi Echeverria Terminologia Adituak Itziar San Martin Jabier Agirre Jon Jatsu Azkue Euskara Zuzentzailea Ander Altuna Idazkaritza Teknikoa Iberba OJS Kudeatzailea Emilio Delgado Ingelesezko aholkularia David Fogarty Harremanetarako info@osagaiz.eus 944 00 11 33